Sistem Tanggung Renteng dengan Akad Kafalah pada Produk Paket Masa Depan (PMD) di BTPN Syariah Pekalongan dalam Perspektif Hukum Islam - Fikri, Ahmad Kamalul; Ubaidillah, Ubaidillah (AHKAM, 2023)
The Future Package (PMD) is an integrated program of the Sharia National Pension Savings Bank provided to a group of women in rural areas who wish to start businesses and have dreams of transforming their lives but do not have access to banking services. Currently, there is a trend among financial institutions, both banks and cooperatives, in mitigating financing risks through the Joint Liability System. From this background, questions arise: (1) How is the joint liability system practiced in the Future Package (PMD) product at BTPN Sharia Pekalongan? (2) What is the Islamic legal perspective on the joint liability system with kafalah contract in the Future Package (PMD) product at BTPN Sharia Pekalongan? This study uses a qualitative descriptive analysis approach aimed at systematically describing the research focus, which includes the joint liability system, where the researcher describes the joint liability system and evaluates it from an Islamic legal perspective. Data collection techniques involve observation, interviews, documentation, and triangulation. The researcher analyzes the data using theories and legal foundations related to joint liability with a kafalah contract, resulting in findings on the mechanism and Islamic legal review of the joint liability system with a kafalah contract in the Future Package (PMD) product at BTPN Sharia Pekalongan. The research findings indicate that the implementation of joint liability in the Future Package (PMD) product at BTPN Sharia Pekalongan is temporary but can become permanent if group members under joint liability run away. The joint liability contract in financing the Future Package (PMD) does not fully comply with Islamic principles, particularly concerning the insurance object, as it is often used for consumable goods instead of business purposes.